Analysis of Spoken Discourse Pattern in Nepali ELT Classes - Dahal, Basudev (Journal of NELTA, 2011)
Among a multitude of study areas, discourse analysis has emerged as a fast-growing discipline because of growing interest of linguists in studying language in natural setting, as opposed to making analyses of artificially created sentences. A concentrated amount of work on discourse analysis in the past few decades has demonstrated that discourse in classrooms is highly organized and amenable to analysis. This paper is an attempt to make an analysis of such a naturally occurring classroom discourse based on Sinclair-Coulthard analysis model developed in 1975.This model has come as a significant contribution for those who are interested in the field of discourse analysis. The study suggests that there is use of a simple discourse pattern in Nepali higher secondary classes of English. Key words: Discourse analysis; Spoken discourse; Discourse structure; Exchange;Move Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 22-27 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4606